2012
DOI: 10.1038/sc.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and antihypertensive treatment in veterans with spinal cord injury and disorders

Abstract: Objectives: Hypertension (HTN) is an important risk factor for cardiovascular disease, a major cause of morbidity and mortality among people with spinal cord injury and disorders (SCI/D). Our study examined prevalence, associated factors, and pharmacological treatment of HTN in Veterans with SCI/D compared with a matched control group. CVD is a major cause of morbidity and mortality in patients with spinal cord injury and disorders (SCI/D). 4-6 Septicemia, respiratory disorders and renal failure were once the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…24,25 The American Heart Association reports increasing prevalence of hypertension with each 10-years increase in age, 24 and the prevalence rates of hypertension reported for individuals with adult-onset SCI mirror these age-related changes. 26,27 In our study population, the odds of having hypertension/cardiac disease were found to increase 4-8% with each additional year of living with a SCI (Table 3). While this pattern of increased odds over time in our participants is similar to that of the general population, the impact of having hypertension/cardiac disease is potentially greater when considering the relative inactivity of individuals with SCI as they are less physically able to attain cardiovascular fitness through lifestyle modifications such as aerobic exercise and maintenance of lean body mass.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…24,25 The American Heart Association reports increasing prevalence of hypertension with each 10-years increase in age, 24 and the prevalence rates of hypertension reported for individuals with adult-onset SCI mirror these age-related changes. 26,27 In our study population, the odds of having hypertension/cardiac disease were found to increase 4-8% with each additional year of living with a SCI (Table 3). While this pattern of increased odds over time in our participants is similar to that of the general population, the impact of having hypertension/cardiac disease is potentially greater when considering the relative inactivity of individuals with SCI as they are less physically able to attain cardiovascular fitness through lifestyle modifications such as aerobic exercise and maintenance of lean body mass.…”
Section: Discussionmentioning
confidence: 67%
“…Alternatively, the greater prevalence of AD in this severity group might have had a confounding effect in increasing the selfreport of hypertension, especially because many individuals who have frequent episodes of AD take antihypertensive medications preventatively. 32 It is likely, however, that the differences among the injury severity groups in ORs of hypertension/cardiac disease occurrence will subsequently change as our study population ages and the prevalence of cardiovascular disease increases, 9,26,30 and thus consistent monitoring of cardiovascular function and appropriate management is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…(15) The relevance of applying these findings derived from studies performed in the general population to persons with SCI has not yet been established. However, CVD is a leading cause of mortality in the SCI population, (37) increased diagnosis of HTN has been reported in veterans with paraplegia compared to veterans with tetraplegia, (38) and increased arterial stiffness is reported among individuals with SCI compared to matched non-SCI controls. (39-41) Furthermore, similar to prior reports (38,42) the present data suggest that nearly three-quarters of the low thoracic population carry the diagnosis of HTN, whereas the significantly reduced prevalence of HTN found in our high thoracic group was fully accounted for by age.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper documented, through medical chart review, the prevalence of HTN diagnosis in veterans without SCI as 68.4% compared to a prevalence of 56.6% in veterans with SCI. (38) We found a similar prevalence of the diagnosis of HTN in our non-SCI veterans, but due to our differentiation of level of injury relative to the origin of sympathetic vasomotor control, our findings in veterans with SCI differ from those reported by Barry et al (38) Specifically, the incidence of the diagnosis of HTN was higher in our veterans with SCI below T7 (72.7%), but the incidence was significantly lower in those with lesions above T6 (≈22%). It is therefore important to consider level of injury relative to peripheral sympathetic vasomotor control when reporting the incidence of HTN in persons with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] Hospitalized Veterans with SCI/D are challenged to control their surroundings due to limited mobility. [5] Consequently, nurses and staff often spend a significant amount of time assisting these patients with basic functions which limits their time to provide clinical care.…”
Section: Figure 1 An Example Of An Ecumentioning
confidence: 99%